2021
DOI: 10.3390/app11178004
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Permanent Teeth Dimensions and Arch Lengths on Dental Crowding during the Mixed Dentition Period

Abstract: Dento-alveolar disharmony with crowding is a common reason for orthodontic treatment with not fully understood or unequivocally demonstrated causes. This study investigated the correlations between teeth dimensions, arch lengths, and crowding during the mixed dentition period. A cross-sectional study on 100 dental casts of patients with class I malocclusions was performed. Dental arches were classified as non-crowded, moderately crowded, severely crowded, and spaced. The mesio-distal widths, bucco-lingual size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In a previously published study, we have concluded that dental crowding in the mixed dentition is associated both with decreased arch lengths, but also with variations of mesiodistal and buccolingual dimensions of permanent incisors and lower first molars [14].…”
Section: Background and Aimsmentioning
confidence: 89%
See 1 more Smart Citation
“…In a previously published study, we have concluded that dental crowding in the mixed dentition is associated both with decreased arch lengths, but also with variations of mesiodistal and buccolingual dimensions of permanent incisors and lower first molars [14].…”
Section: Background and Aimsmentioning
confidence: 89%
“…Regarding possible correlations between dental morphology and arch crowding, studies conducted on permanent dentition and mixed dentition demonstrated the existence of variations in mesiodistal, buccolingual, and crown proportions of permanent incisors and lower permanent first molars in patients with arch crowding [14,26].…”
Section: Discussionmentioning
confidence: 99%